Inovasi untuk Perubahan: Strategi Inovatif Mengatasi Krisis Energi, Pangan, dan Lingkungan Hidup di Masa Pemanasan Global - Gultom, Latifah Hannum; Simanjuntak, Eunike; Rusnita, Ayu Novidaniati; Sinaga, Rahma Dhani Fitria; Febriana, Febriana; Tarigan, Fandy; Saragih, Theresia J.R (Sublim: Jurnal Pendidikan, 2024)
Global warming is a major challenge that threatens the stability of the global ecosystem, resulting in energy, food and environmental crises. To overcome this problem, an innovative strategy that is sustainable and adaptive is needed. This article explores various innovations that can be effective solutions in dealing with this crisis. In the energy sector, the development of renewable energy technologies such as solar, wind and biomass power shows great potential to replace dwindling fossil energy sources. In the food sector, sustainable agricultural innovation through precision farming techniques, hydroponics and agroforestry can increase food security while reducing environmental impacts. The research method used in this research is a qualitative method, namely research carried out by collecting data or scientific writing which aims to collect research data in the form of library data that has been selected, searched, presented and analyzed. The data collection technique uses journal materials, e-books and comes from previous research. The results of the research explain that in facing the energy, food and environmental crises in the era of global warming, innovation is the main key to creating positive change. Innovative strategies that include the development of environmentally friendly technologies, sustainable resource management, and collaborative approaches between sectors will be the main drivers in overcoming these challenges. Innovations in renewable energy technologies such as solar panels, wind power, and geothermal energy can help reduce dependence on fossil fuels and reduce greenhouse gas emissions.